A Simple and Fast Procedure for Dissolution of An Oxide Fuel Fragment to Extract Its Retained Fission Gases - Park, Soon-Dal; Kim, Jung-Suk; Ha, Yeong-Keong; Song, Kyuseok (Asian Journal of Chemistry, 2012)
A fast and simple dissolution procedure using a commercially available electrode furnace has been developed to extract the retained fission gases in an oxide fuel fragment. A commercial hydrogen analyzer equipped with an electrode furnace was applied in the fusion experiments of a fresh, non-irradiated oxide fuel fragment. Approximately 0.1-0.2 g fragments of an oxide fuel were fused with a single flux and/or multiple fluxes such as tin, nickel, or copper, while varying the fusion current and time. After fusion of the oxide fuel fragment, the melting state of the resultant melt was investigated using an electron microscope, an X-ray diffraction spectrometer (XRD) and an inductively coupled plasma-atomic emission spectrometer (ICP-AES). A fresh UO2 fragment (ca. 0.1 g) for a pressurized water reactor (PWR) was melted completely with ca. 1 g of a metallic flux, such as tin or nickel at a fusion current of 800 A and a fusion time of 50 s as an uranium-metal (flux) alloy. However, complete fusion of a simulated spent fuel (SIMFUEL) fragment with a burnup of 60 GWd/tU requires a higher fusion current, 850 A and a longer fusion time, 120 s and simultaneous double metal fluxing, using tin and nickel. Since the physicochemical properties of SIMFUEL and spent oxide fuel are very similar, the fusion conditions may be applicable for fusion of the latter as well.